A)
The Pythagorean theorem states that the sum of the squared legs is the squared hypothenuse:
![a^2+b^2=c^2](https://img.qammunity.org/2019/formulas/mathematics/high-school/sjkaahpsyltp8n99but72kh8jxe05yu3k3.png)
If we divide the whole expression by
, we have
![(a^2)/(c^2) + (b^2)/(c^2) = (c^2)/(c^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/bqk4ski8tkk3eu7klyzjhbhmdnyo6mkvh0.png)
B)
The sine of x is the ratio between the opposite leg and the hypothenuse, while the cosine of x is the ratio between the adjacent leg and the hypothenues:
![\sin(x) = (a)/(c),\quad \cos(x) = (b)/(c)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/h387lvbcya3dhmd9u5js9tg318oiipc11g.png)
This means that
![\sin^2(x) = \left((a)/(c)\right)^2 = (a^2)/(c^2),\quad \cos^2(x) = \left((b)/(c)\right)^2 = (b^2)/(c^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3jicga2tb63hdgxrvi62zlf794r5lt72ge.png)
C)
From part B, we know that
![\sin^2(x)+\cos^2(x) = (a^2)/(c^2) + (b^2)/(c^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zjujhcspf1dysz3kuubn9upyh9m3pkvt41.png)
From part A, we know that this sum equals
![\sin^2(x)+\cos^2(x) = (a^2)/(c^2) + (b^2)/(c^2)=(c^2)/(c^2)=1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/80235au3wno04gbc5mfrwjlakktoa45zjn.png)
Which terminates the proof.